(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This study investigated the process of transpiration in plants under in vitro (laboratory) and in vivo (natural) conditions using four genotypes: S-46, S-73, S-55, and S-17. Results demonstrated that the transpiration rate was significantly higher in vivo compared to in vitro. The highest rate was observed in genotype S-17, indicating its superior adaptability to environmental stresses such as drought and salinity. The study highlights the importance of understanding plant water regulation mechanisms under varying conditions and presents genotype S-17 as a promising candidate for cultivation in arid and saline soils.